EFFICIENCY IN INDIA: AN EMPIRICAL STUDY OF PUBLIC AND PRIVATE SECTOR - Mittal, Palak; Singh, Ravi Inder (Gyan Management Journal, 2024)
This study delves into the Total Factor Productivity (TFP) growth  of major Indian private and public sector banks from 2012 to 2022,  employing the Malmquist Productivity Index and Data Envelopment  Analysis (DEA). It scrutinizes TFP change, technical change, and  efficiency change within the banking sector. Among public sector  banks, approximately 58% exhibit positive productivity changes,  contrasting with the increased productivity of private banks  displaying 31.5%. Significant differences in TFP become evident, with  Canara Bank ranking highest among public sector banks, achieving  a TFP score of 1.059, while Punjab National Bank exhibits the lowest  TFP, averaging at 0.948. In the private sector, Axis Bank emerges as  the frontrunner with an average TFP of 1.145, whereas Tamil Nadu  Mercantile Bank lags behind with an average TFP of 0.381. These  findings furnish policymakers and stakeholders with crucial insights  to formulate strategies aimed at bolstering the technical efficiency  of both private and public sector banks in India, significant for the  sector’s sustained growth and stability.
Keywords: Public Sector Banks; Private Sector; Economy; Data Envelopment Analysis